2017
DOI: 10.1371/journal.pone.0173707
|View full text |Cite
|
Sign up to set email alerts
|

Optokinetic nystagmus reflects perceptual directions in the onset binocular rivalry in Parkinson’s disease

Abstract: Optokinetic nystagmus (OKN), the reflexive eye movements evoked by a moving field, has recently gained interest among researchers as a useful tool to assess conscious perception. When conscious perception and stimulus are dissociated, such as in binocular rivalry—when dissimilar images are simultaneously presented to each eye and perception alternates between the two images over time—OKN correlates with perception rather than with the physical direction of the moving field. While this relationship is well esta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 52 publications
4
22
0
Order By: Relevance
“…This is also consistent with our study in (onset) binocular rivalry in which DBS, but not dopaminergic drugs, facilitated perceptual decisions. 38 Moreover, this facilitation effect was seen in perceptual decisions during complex binocular rivalry, but not in simpler non-rivalrous situations. 38 The STN is hypothesised to act as a brake in the cortical-striatal network, increasing the threshold of evidence required to make a complex decision when there are conflicting cuesa process thought to be disrupted by STN-DBS.…”
Section: Reach Movement Metricsmentioning
confidence: 92%
See 1 more Smart Citation
“…This is also consistent with our study in (onset) binocular rivalry in which DBS, but not dopaminergic drugs, facilitated perceptual decisions. 38 Moreover, this facilitation effect was seen in perceptual decisions during complex binocular rivalry, but not in simpler non-rivalrous situations. 38 The STN is hypothesised to act as a brake in the cortical-striatal network, increasing the threshold of evidence required to make a complex decision when there are conflicting cuesa process thought to be disrupted by STN-DBS.…”
Section: Reach Movement Metricsmentioning
confidence: 92%
“…38 Moreover, this facilitation effect was seen in perceptual decisions during complex binocular rivalry, but not in simpler non-rivalrous situations. 38 The STN is hypothesised to act as a brake in the cortical-striatal network, increasing the threshold of evidence required to make a complex decision when there are conflicting cuesa process thought to be disrupted by STN-DBS. 15 How STN-DBS does this is not fully understood.…”
Section: Reach Movement Metricsmentioning
confidence: 92%
“…As horizontal smooth pursuit tends to follow perceived horizontal motion (Enoksson, 1963;Merrill and Stark, 1963;Fujiwara et al, 2017;Frässle et al, 2014), we inferred perceived motion from horizontal velocity of smooth eye movements. In principle, zerocrossings of horizontal eye velocity may indicate reversals of perceived motion.…”
Section: Estimate Of Perceived Motionmentioning
confidence: 99%
“…Typically, the recorded eye velocity is processed and filtered to extract the slow ('pursuit') phase of OKN (Naber et al, 2011;Frässle et al, 2014;Fujiwara et al, 2017) and slow velocity is categorized in a binary fashion, such as to identify periods with a consistent direction of perceived motion ('dominance periods'). While this approach reliably identifies long dominance periods, shorter periods of either dominance or transition are more difficult to resolve.…”
Section: Introductionmentioning
confidence: 99%
“…Due to variations in the frequency and duration of PFI per participant, averaging data over participants is not straightforward. To resolve this, we performed image-based event-by-event analyses (Fujiwara et al, 2017) to investigate whether the amount of PFI reported may reflect changes in log(SNR). Within each participant, all PFI events were sorted in descending order based on the sum of buttons pressed at each time point, and over a 2.5 second time window (detailed below) per disappearance/reappearance event.…”
Section: Event-by-event Image Analysis Of Button Press and Ssvep-snrmentioning
confidence: 99%